1999
DOI: 10.1677/joe.0.1630523
|View full text |Cite
|
Sign up to set email alerts
|

PDX-1 and Msx-2 expression in the regenerating and developing pancreas

Abstract: We have observed pancreatic duct cell proliferation and islet regeneration in transgenic mice whose pancreata produce interferon (IFNg mice). We have previously demonstrated that new islet cells derive from endocrine progenitor cells in the pancreatic ducts of this model. The current study was initiated to define these endocrine progenitor cells further and to identify novel markers associated with pancreatic regeneration. Importantly, we have found that PDX-1, a transcription factor required for insulin gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 27 publications
3
68
0
1
Order By: Relevance
“…As a result, pdx1 mutants lack functional pancreatic tissue (Jonsson et al, 1994;Offield et al, 1996), and it has been suggested that pdx1 regulates pancreatic stem cell function. Consistent with this hypothesis, pdx1 expression is markedly increased in proliferating ductular cells during pancreatic regeneration (Kritzik et al, 1999;Sharma et al, 1999).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…As a result, pdx1 mutants lack functional pancreatic tissue (Jonsson et al, 1994;Offield et al, 1996), and it has been suggested that pdx1 regulates pancreatic stem cell function. Consistent with this hypothesis, pdx1 expression is markedly increased in proliferating ductular cells during pancreatic regeneration (Kritzik et al, 1999;Sharma et al, 1999).…”
supporting
confidence: 68%
“…1Q-X). To determine whether the mechanism underlying pancreatic recovery resembled mammalian pancreatic regeneration (Kritzik et al, 1999;Sharma et al, 1999), we analyzed cell proliferation in 48, 60, and 72 hpf pdx1 morphants using 5-bromo-2Ј-deoxyuridine immunohistochemistry. These data revealed that proliferating cells in the pancreas of pdx1 morphants were present within tissue surrounding the islet in the region of the developing exocrine pancreas but never within the islet (Fig.…”
mentioning
confidence: 99%
“…These findings are in good agreement with earlier studies in mice and human pancreata, and therefore substantiate our observations in normal and pathologic gastric mucosa. 11,13 Although PDX-1 acts as a transcription factor, it can also be found in an inactive form in the cytoplasmic compartment. Activation and nuclear translocation in pancreatic cells were shown to be regulated by glucose.…”
Section: Discussionmentioning
confidence: 99%
“…8 It specifically recognizes PDX-1 on Western blots 9,10 and was also used in several immunohistochemical studies in the developing and regenerating pancreas. 11 Binding of the primary antibodies was detected using biotinylated swine anti-rabbit antisera (1:50; Dako, Hamburg, Germany), and a streptavidin-biotinylated alkaline phosphatase complex (Dako). Fast Red (Sigma-Aldrich, Taufkirchen, Germany) was employed as chromogen.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Activation of Pdx1 in duct cells of the pancreas has also been observed following partial pancreatectomy in mice [85] and in insulin resistant Zucker fatty (ZF) rats [83]. Importantly in this regard, Pdx1 expression is often observed in proliferating duct cells [77,94,95], and such cells have been suggested to serve as substrate for β cell neogenesis, particularly in cases of adaptive hyperplasia or pancreas regeneration [92,[96][97][98][99]. A recent study suggests that Pdx1, in complex with TALE transcription factors, negatively regulates the duct-specific keratin 19 gene in mature duct cells [100].…”
Section: Role Of Pdx1 In Adaptive β Cell Hyperplasia and β Cell Regenmentioning
confidence: 99%